One price fits all? Wind power expansion under uniform and nodal pricing in Germany - Lukas Schmidt; Jonas Zinke (Institute of Energy Economics at the University of Cologne (EWI), 2020)
This paper evaluates investment incentives for wind power under uniform and nodal pricing.An electricity system model is developed, which allows for investments into wind power whileconsidering transmission grid constraints in detail. Targeting equally high wind capacitiesunder nodal and uniform pricing until 2030, locations of new wind power plants shift towardssites with lower wind yield under nodal prices. The wind energy fed into the grid, though, ishigher under nodal pricing since curtailment is cut to a third. Grid-optimal wind locationsrequire higher subsidy payments but decrease yearly variable supply costs by 1.5% in 2030.However, distributional effects are an obstacle to implementing nodal pricing, where about75% of German demand faces electricity costs increase of about 5%. For mitigating distortedinvestment signals of uniform pricing, implementing investment restrictions within grid ex-pansion areas prove to be more promising than a latitude-dependent generator-componentin the grid tariff design.
Keywords: Q42; Q48; C61; D47; 330; Nodal pricing; Market design; Energy System Modeling; Renewable Energies; Market Values